Analysis of the Application of Statements of Financial Accounting Standards Number 71 concerning Financial Instruments (Case Study at Ltd Bank BRI (Persero) Plc in 2020) - Adriansyah, Mohamad Vikri; Challen, Auliffi Ermian (Indonesian Operations Research Association (IORA), 2022)
Statements of Financial Accounting Standards are commonly called PSAK in Indonesian terms. PSAK No. 71, which is the adoption of International Financial Reporting Standards (IFRS) 9, has officially come into force effective as of 1 January 2020 as Indonesia's new Financial Accounting Standards are commonly called SAK in Indonesian terms. PSAK No. 71 changed several rules related to financial instruments. This emerged as a response to the failure of corporations, especially the financial sector, which could not see signals from the market regarding uncollected bills from the start. This study aims to determine the application of PSAK No. 71 Financial Instruments in the financial sector, especially in the banking industry. The subject in this study is Ltd Bank BRI (Persero) Plc because Ltd Bank BRI (Persero) Plc is the Bank with the largest total assets and the Bank with the highest credit distribution value in Indonesia in 2020. The object in this study is the financial statements of Ltd Bank BRI (Persero) Plc ending as of December 31, 2020. This research type of research is descriptive qualitative with a case study approach. The results showed that Ltd Bank BRI (Persero) Plc had implemented all the regulations contained in PSAK No. 71 for the financial statements ended December 31, 2020, and the impact of implementation can be seen from the total value of Allowance for Impairment Losses are commonly called CKPN in Indonesian terms which increased by 29.07% at the beginning of its implementation.